2004
DOI: 10.1002/app.20369
|View full text |Cite
|
Sign up to set email alerts
|

The effect of maleic anhydride modified polypropylene on the mechanical properties of feather fiber, kraft pulp, polypropylene composites

Abstract: Composites made of feather fiber (Ff), kraft pulp fiber (Pf), polypropylene (PP), and maleic anhydride modified polypropylene (MaPP) were tested in tension and three-point bend tests. Composite panels were compression molded from multiple plies of nonwoven, fabric-like prepreg manufactured with wetlay papermaking equipment. Composites containing all four materials were manufactured with MaPP substitutions for PP of 0 -10 wt % at 2 wt % increments. The best mechanical properties were observed with a substitutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
69
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 14 publications
3
69
0
2
Order By: Relevance
“…Among all the reinforcement materials, glass fibers attracted much attention die to their better physicomechanical properties, good corrosion resistance, and good absorption and insulation properties. The most widely used glass fiber is E-glass fiber, which has good insulation properties and can maintain properties up to 815 C. The composition of E-glass fiber is 54.3SiO 2 -15.2Al 2 O 3 -17.2CaO-4.7MgO-8.0BO-0.6Na 2 O [1][2][3][4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…Among all the reinforcement materials, glass fibers attracted much attention die to their better physicomechanical properties, good corrosion resistance, and good absorption and insulation properties. The most widely used glass fiber is E-glass fiber, which has good insulation properties and can maintain properties up to 815 C. The composition of E-glass fiber is 54.3SiO 2 -15.2Al 2 O 3 -17.2CaO-4.7MgO-8.0BO-0.6Na 2 O [1][2][3][4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…Water is lost when the concrete dries and physical properties may have been maintained. Bullions et al [41,42] prepare composites of kenaf bast, wood pulp, and poultry feather fiber with polypropylene using a wetlay process. For feather fiber/PP composites, modifying PP with maleic anhydride to increase fiber/ polymer interactions increases the physical properties of the composites.…”
Section: Introductionmentioning
confidence: 99%
“…The bast fibers such as jute, flax, hemp, ramie, sisal, kenaf are presently using as reinforcement in polymer composite and many efforts have been made by researchers to establish natural biodegradable fiber as substitute of synthetic fiber to use effectively in the composite material. Several studies reported that incorporation of lingo-cellulosic fiber improves the physicomechanical properties of polymer matrices in the composite material [1][2][3][4][5][6][7][8][9][10][11][12][13]. Scientists prefer thermoplastic composites than thermoset because of low production cost and lower processing cycle.…”
Section: Introductionmentioning
confidence: 99%